Method for manufacturing solid oxide type electrolytic cell
The method addresses the stress-induced cracking issue in SOEC by using nickel oxide and ceramic materials for the anode and controlling dimensional changes through heat treatment, resulting in a more durable solid oxide electrolytic cell.
Patent Information
- Application Number
- JP2023153937
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Solid oxide electrolytic cells (SOEC) face challenges due to differing gas pressures and stresses when used for oxygen consumption in SOFC versus oxygen generation, leading to potential cracks in the solid electrolyte.
A method for manufacturing a solid oxide electrolytic cell involves using nickel oxide and ceramic materials with oxygen ion conductivity for the anode, controlling pore formation, and optimizing heat treatment in a reducing atmosphere to manage dimensional changes and residual strain within specific limits.
This manufacturing method effectively prevents cracks in the solid electrolyte during the operation of SOEC, enhancing the durability and reliability of the cells.
Smart Images

Figure 2025045901000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a solid oxide electrolysis cell. [Background technology]
[0002] Solid oxide fuel cells (hereinafter referred to as "SOFCs") are known that generate electricity by utilizing an electrochemical reaction between hydrogen and oxygen. For example, a single fuel cell, which is a constituent unit of the SOFC described in Patent Document 1, includes an electrolyte layer containing a solid oxide, an air electrode disposed on one side of the electrolyte layer, and a fuel electrode disposed on the other side of the electrolyte layer. Oxygen ions dissociated from oxygen supplied to the air electrode move to the fuel electrode based on the oxygen conductivity of the solid electrolyte, and react with hydrogen contained in the fuel gas supplied to the fuel electrode to generate water vapor and electricity.
[0003] The above-mentioned SOFC can be used as a solid oxide electrolysis cell (hereinafter simply referred to as "SOEC") by passing current in the reverse direction, and is known to be used as an energy storage technology in the form of converting water vapor into hydrogen using surplus electricity, which is an issue in the process of introducing renewable energy. When water vapor is supplied to the fuel electrode and an electric current is passed between the air electrode and the fuel electrode, the water vapor is electrolyzed and hydrogen is generated from the fuel electrode, and oxygen ions generated at the fuel electrode move to the air electrode due to the oxygen conductivity of the solid electrolyte, and oxygen is generated from the air electrode. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2023-080459 A Summary of the Invention [Problem to be solved by the invention]
[0005] Generally, in SOFCs, oxygen is consumed at the fuel electrode during use, resulting in a decrease in gas pressure. However, in SOECs, oxygen is generated at the air electrode during use, resulting in an increase in gas pressure, which in turn results in stresses different from those in SOFCs and may cause cracks to form in the solid electrolyte. [Means for solving the problem]
[0006] The present disclosure can be realized in the following forms.
[0007] (1) According to one embodiment of the present disclosure, there is provided a method for producing a solid oxide electrolysis cell. The method for producing a solid oxide electrolysis cell includes an anode, an air electrode, and a solid electrolyte layer provided between the anode and the air electrode, the anode being formed using nickel oxide and a ceramic material having oxygen ion conductivity as materials, and pores being formed in the anode. The method includes a step of heat treating the anode in a non-reduced state to a reduced state by a reducing atmosphere, in which LI denotes a dimension of the anode at the beginning of the step, LR denotes a dimension of the anode at the end of the step, and ΔL(%) is ΔL={(LR-LI) / LI}×100, where ΔL(%) is -0.05% or more and 0% or less. According to this embodiment of the method for producing a solid oxide electrolysis cell, it is possible to suppress the occurrence of cracks in the solid electrolyte during use of the solid oxide electrolysis cell.
[0008] (2) In the method for producing a solid oxide electrolysis cell described in (1) above, the residual strain S (%) generated in the solid electrolyte layer may be expressed by the following formula (1) and may be −2.5% or more and −0.5% or less. According to this form of the method for producing a solid oxide electrolysis cell, it is possible to more effectively prevent cracks from occurring in the solid electrolyte during use of the solid oxide electrolysis cell.
[0009]
number
[0010] (3) In the method for producing a solid oxide electrolysis cell described in (1) or (2) above, the anode may include, in order from the solid electrolyte layer side, an anode functional layer and an anode substrate layer having a higher porosity than the anode functional layer. This form of the method for producing a solid oxide electrolysis cell can ensure the strength of the anode functional layer.
[0011] (4) In the method for producing a solid oxide electrolysis cell according to any one of (1) to (3) above, a fuel gas containing water vapor is supplied to the fuel electrode at a rate of 100 to 130 liters / (min cm 2 ) may be supplied at a flow rate of 100 to 2000 kPa (100 / s) for use. In the solid oxide electrolysis cell of this embodiment, hydrogen and oxygen are generated during use of the solid oxide electrolysis cell, causing stress on the solid electrolyte layer. However, in accordance with this manufacturing method, it is possible to suppress the occurrence of cracks in the solid electrolyte during use of the solid oxide electrolysis cell.
[0012] (5) In the method for producing a solid oxide electrolysis cell according to any one of (1) to (4) above, a gas containing oxygen is supplied to the air electrode at a rate of 30 to 50 liters / (min cm 2 ) may be supplied at a flow rate of 100 to 2000 kPa (100 / s) for use. In the solid oxide electrolysis cell of this embodiment, hydrogen and oxygen are generated during use of the solid oxide electrolysis cell, causing stress on the solid electrolyte layer. However, in accordance with this manufacturing method, it is possible to suppress the occurrence of cracks in the solid electrolyte during use of the solid oxide electrolysis cell.
[0013] (6) In the method for producing a solid oxide electrolysis cell according to any one of (1) to (5) above, a fuel gas containing water vapor is supplied to the fuel electrode at a rate of 100 to 130 liters / (min cm 2 ), and the air electrode is supplied with an oxygen-containing gas at a flow rate of 30 to 50 liters / (min cm 2) may be supplied at a flow rate of 100 to 2000 kPa (100 / s) for use. In the solid oxide electrolysis cell of this embodiment, hydrogen and oxygen are generated during use of the solid oxide electrolysis cell, causing stress on the solid electrolyte layer. However, in accordance with this manufacturing method, it is possible to suppress the occurrence of cracks in the solid electrolyte during use of the solid oxide electrolysis cell.
[0014] (7) In the method for producing a solid oxide electrolysis cell according to any one of (1) to (6), the volume of the air chamber facing the air electrode is 9 cm 3 ~11cm 3 According to the solid oxide electrolysis cell of this embodiment, hydrogen and oxygen are generated during use of the solid oxide electrolysis cell, causing stress on the solid electrolyte layer (hereinafter also referred to as "electrolyte layer"), but according to this manufacturing method, it is possible to suppress the occurrence of cracks in the solid electrolyte during use of the solid oxide electrolysis cell.
[0015] The present invention can be realized in various forms, for example, in the form of a solid oxide electrolysis cell. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a perspective view showing the external configuration of a stack of electrolysis cells in the present embodiment. [Diagram 2] FIG. 2 is an explanatory diagram showing an XZ cross-sectional configuration of the stack taken along the line II-II in FIG. [Diagram 3] FIG. 3 is an explanatory diagram showing a YZ cross-sectional configuration of the stack taken along the line III-III in FIG. [Figure 4] 3 is an explanatory diagram showing the XZ cross-sectional configuration of two adjacent units at the same position as the cross-section shown in FIG. 2. [Diagram 5] 4 is an explanatory diagram showing the YZ cross-sectional configuration of two adjacent units at the same position as the cross-section shown in FIG. 3. [Figure 6] FIG. 2 is a schematic diagram showing the configuration of a unit cell according to the embodiment of the present invention. [Figure 7] FIG. 1 is a process diagram showing an example of a manufacturing method for a single SOEC cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A. First embodiment: A-1.Configuration: (Configuration of electrolysis cell stack 100) FIG. 1 is a perspective view showing the external configuration of a stack 100 of an electrolysis cell in this embodiment, FIG. 2 is an explanatory diagram showing an XZ cross-sectional configuration of the stack 100 at a position II-II in FIG. 1, and FIG. 3 is an explanatory diagram showing a YZ cross-sectional configuration of the stack 100 at a position III-III in FIG. 1. Each figure shows mutually orthogonal XYZ axes for specifying directions. In this specification, for convenience, the positive direction of the Z axis is referred to as the "upward direction" and the negative direction of the Z axis is referred to as the "downward direction", but the stack 100 may actually be installed in a direction different from such directions. The same applies to FIG. 4 and subsequent figures.
[0018] The stack 100 in this embodiment is a stack of solid oxide electrolysis cells (SOEC). The stack 100 includes a plurality of (seven in this embodiment) units 102 and a pair of end plates 104, 106. The seven units 102 are arranged side by side in a predetermined arrangement direction (Z-axis direction (vertical direction) in this embodiment). The pair of end plates 104, 106 are arranged to sandwich the assembly made up of the seven units 102 from above and below.
[0019] A plurality of holes (eight in this embodiment) penetrating in the Z-axis direction are formed in the peripheral portion around the Z-axis direction of each layer (units 102, end plates 104, 106) constituting stack 100, and corresponding holes formed in each layer communicate with each other in the Z-axis direction to form communication holes 108 extending in the Z-axis direction from one end plate 104 to the other end plate 106. In the following description, the holes formed in each layer of stack 100 to form communication holes 108 are also referred to as "communication holes 108."
[0020] A bolt 22 extending in the Z-axis direction is inserted into each communication hole 108, and the stack 100 is fastened by the bolt 22 and a nut 24 fitted on both sides of the bolt 22. As shown in FIG. 2 and FIG. 3, an insulating sheet 26 is interposed between the nut 24 fitted on one side (upper side) of the bolt 22 and the upper surface of the end plate 104 constituting the upper end of the stack 100, and between the nut 24 fitted on the other side (lower side) of the bolt 22 and the lower surface of the end plate 106 constituting the lower end of the stack 100. However, at a location where a gas passage member 27 described later is provided, the gas passage member 27 and the insulating sheets 26 arranged on the upper and lower sides of the gas passage member 27 are interposed between the nut 24 and the surface of the end plate 106. The insulating sheet 26 is composed of, for example, a mica sheet, a ceramic fiber sheet, a ceramic powder sheet, a glass sheet, a glass ceramic composite, or the like.
[0021] The outer diameter of the shaft of each bolt 22 is smaller than the inner diameter of each communication hole 108. Therefore, a space is secured between the outer peripheral surface of the shaft of each bolt 22 and the inner peripheral surface of each communication hole 108. As shown in FIG. 1 and FIG. 2, a space formed by a bolt 22 (bolt 22A) located near the midpoint of one side (the side on the positive side of the X-axis among two sides parallel to the Y-axis) on the outer periphery around the Z-axis direction of the stack 100 and the communication hole 108 into which the bolt 22A is inserted functions as an air electrode gas supply manifold 161. The air electrode gas supply manifold 161 is a gas flow path through which the air electrode gas OG is introduced from the outside of the stack 100 by a blower, pump, or the like (not shown) and supplies the air electrode gas OG to each unit 102. A space formed by a bolt 22 (bolt 22B) located near the midpoint of the opposite side (the side on the negative X-axis side of the two sides parallel to the Y-axis) and the communication hole 108 into which the bolt 22B is inserted functions as an air electrode gas discharge manifold 162. The air electrode gas discharge manifold 162 discharges air electrode off-gas OOG, which is gas discharged from the air chamber 166 of each unit 102, to the outside of the stack 100. In this embodiment, air is used as the air electrode gas OG, but oxygen gas may be used instead of air.
[0022] 1 and 3, a space formed by a bolt 22 (bolt 22D) located near the midpoint of one side (the side on the Y-axis positive side of two sides parallel to the X-axis) on the outer periphery around the Z-axis direction of the stack 100 and the communication hole 108 into which the bolt 22D is inserted functions as a fuel gas supply manifold 171. The fuel gas supply manifold 171 is a gas flow path into which the fuel gas FG is introduced from the outside of the stack 100 by a blower, pump, or the like (not shown) and supplies the fuel gas FG to each unit 102. A space formed by a bolt 22 (bolt 22E) located near the midpoint of the side opposite to the side (the side on the Y-axis negative side of two sides parallel to the X-axis) and the communication hole 108 into which the bolt 22E is inserted functions as a fuel gas discharge manifold 172. The fuel gas exhaust manifold 172 exhausts fuel off-gas FOG, which is gas exhausted from the fuel chamber 176 of each unit 102, to the outside of the stack 100. In this embodiment, water vapor is used as the fuel gas FG.
[0023] The stack 100 is provided with four gas passage members 27. Each gas passage member 27 has a hollow cylindrical main body 28 and a hollow cylindrical branch portion 29 branched from a side surface of the main body 28. A hole of the branch portion 29 communicates with a hole of the main body 28. A gas pipe (not shown) is connected to the branch portion 29 of each gas passage member 27. As shown in FIG. 2, a hole of the main body 28 of the gas passage member 27 arranged at the position of the bolt 22A forming the air electrode gas supply manifold 161 communicates with the air electrode gas supply manifold 161, and a hole of the main body 28 of the gas passage member 27 arranged at the position of the bolt 22B forming the air electrode gas discharge manifold 162 communicates with the air electrode gas discharge manifold 162. Also, as shown in FIG. 3, the hole in main body 28 of gas passage member 27 arranged at the position of bolt 22D that forms fuel gas supply manifold 171 is connected to fuel gas supply manifold 171, and the hole in main body 28 of gas passage member 27 arranged at the position of bolt 22E that forms fuel gas exhaust manifold 172 is connected to fuel gas exhaust manifold 172.
[0024] (Configuration of end plates 104, 106) The pair of end plates 104, 106 are conductive members having a substantially rectangular flat plate shape, and are formed of, for example, stainless steel. One end plate 104 is disposed above the uppermost unit 102, and the other end plate 106 is disposed below the lowermost unit 102. The multiple units 102 are sandwiched between the pair of end plates 104, 106 in a pressed state. The upper end plate 104 functions as a positive terminal of the stack 100, and the lower end plate 106 functions as a negative terminal of the stack 100.
[0025] (Unit 102 Configuration) FIG. 4 is an explanatory diagram showing the XZ cross-sectional configuration of two adjacent units 102 at the same position as the cross-section shown in FIG. 2, and FIG. 5 is an explanatory diagram showing the YZ cross-sectional configuration of two adjacent units 102 at the same position as the cross-section shown in FIG. 3.
[0026] 4 and 5, the unit 102 includes a single cell 110, a separator 120, an air electrode side frame 130, an air electrode side current collector 134, an anode side frame 140, an anode side current collector 144, a spacer 149, and a pair of interconnectors 150 constituting the uppermost and lowermost layers of the unit 102. Holes corresponding to the communication holes 108 through which the above-mentioned bolts 22 are inserted are formed in the peripheral portions around the Z direction of the separator 120, the air electrode side frame 130, the anode side frame 140, and the interconnector 150.
[0027] The interconnector 150 is a conductive member having a substantially rectangular flat plate shape, and is formed of, for example, ferritic stainless steel. The interconnector 150 ensures electrical conduction between the units 102 and prevents the reaction gases from mixing between the units 102. In this embodiment, when two units 102 are arranged adjacent to each other, one interconnector 150 is shared by the two adjacent units 102. That is, the upper interconnector 150 in a certain unit 102 is made of the same material as the lower interconnector 150 in another unit 102 adjacent to the upper side of the unit 102. In addition, since the stack 100 includes a pair of end plates 104, 106, the upper interconnector 150 is omitted in the unit 102 located at the top of the stack 100, and the lower interconnector 150 is omitted in the unit 102 located at the bottom (see FIG. 2 and FIG. 3).
[0028] The unit cell 110 includes an electrolyte layer 112, and an air electrode (anode) 114 and a fuel electrode (cathode) 116 that face each other in the Z-axis direction (the arrangement direction in which the units 102 are arranged) with the electrolyte layer 112 in between. That is, the air electrode 114 and the fuel electrode 116 face each other in the Z-axis direction with the electrolyte layer 112 in between. The unit cell 110 of this embodiment is an anode-supported type unit cell in which the electrolyte layer 112 and the air electrode 114 are supported by the fuel electrode 116.
[0029] The electrolyte layer 112 is a substantially rectangular flat-plate member as viewed in the Z-axis direction, and is a dense layer (with low porosity). The air electrode 114 is a substantially rectangular flat-plate member smaller than the electrolyte layer 112 as viewed in the Z-axis direction, and is a porous layer (with a higher porosity than the electrolyte layer 112 in this embodiment). The fuel electrode 116 is a substantially rectangular flat-plate member having substantially the same size as the electrolyte layer 112 as viewed in the Z-axis direction, and is a porous layer (with a higher porosity than the electrolyte layer 112 in this embodiment). The unit cell 110 of this embodiment having such a configuration is a solid oxide electrolysis cell (SOEC) that uses a solid oxide as an electrolyte. The detailed configuration of the unit cell 110 will be described later.
[0030] The separator 120 is a frame-like member having a substantially rectangular hole 121 formed near the center and penetrating in the Z-axis direction, and is made of, for example, metal. The periphery of the hole 121 in the separator 120 faces the peripheral portion of the surface of the electrolyte layer 112 on the air electrode 114 side. The separator 120 is joined to the electrolyte layer 112 (single cell 110) by a joint 124 formed of a brazing material (for example, Ag brazing) arranged in the facing portion. The separator 120 partitions an air chamber 166 facing the air electrode 114 and a fuel chamber 176 facing the fuel electrode 116, thereby suppressing gas leakage from one electrode side to the other electrode side at the peripheral portion of the single cell 110.
[0031] The air electrode side frame 130 is a frame-like member having a substantially rectangular hole 131 formed near the center and penetrating in the Z-axis direction, and is formed of an insulator such as mica. The hole 131 of the air electrode side frame 130 constitutes an air chamber 166 facing the air electrode 114. The air electrode side frame 130 is in contact with the peripheral portion of the surface of the separator 120 opposite to the side facing the electrolyte layer 112, and the peripheral portion of the surface of the interconnector 150 facing the air electrode 114. The air electrode side frame 130 also electrically insulates the pair of interconnectors 150 included in the unit 102. The air electrode side frame 130 also has an air electrode gas supply communication hole 132 that communicates between the air electrode gas supply manifold 161 and the air chamber 166, and an air electrode gas discharge communication hole 133 that communicates between the air chamber 166 and the air electrode gas discharge manifold 162. The air flow rate per unit area entering the air chamber 166 can be adjusted by appropriately changing the size of the air electrode gas supply communication hole 132 and the flow rates of the blower, pump, etc. Similarly, the air discharge rate per unit area leaving the air chamber 166 can be adjusted by changing the size of the air electrode gas discharge communication hole 133.
[0032] The fuel electrode side frame 140 is a frame-like member having a substantially rectangular hole 141 formed near the center and penetrating in the Z-axis direction, and is made of, for example, metal. The hole 141 of the fuel electrode side frame 140 constitutes a fuel chamber 176 facing the fuel electrode 116. The fuel electrode side frame 140 is in contact with the peripheral portion of the surface of the separator 120 facing the electrolyte layer 112 and the peripheral portion of the surface of the interconnector 150 facing the fuel electrode 116. The fuel electrode side frame 140 is also formed with a fuel gas supply passage 142 that communicates the fuel gas supply manifold 171 with the fuel chamber 176, and a fuel gas discharge passage 143 that communicates the fuel chamber 176 with the fuel gas discharge manifold 172. The fuel gas flow rate per unit area entering the fuel chamber 176 can be adjusted by appropriately changing the size of the fuel electrode gas supply passage 142, the flow rate of the blower, the pump, etc. Similarly, by changing the size of the anode gas discharge passage 143, the amount of fuel discharged per unit area from the fuel chamber 176 can be adjusted.
[0033] The fuel electrode side current collector 144 is disposed in the fuel chamber 176. The fuel electrode side current collector 144 includes an interconnector facing portion 146, an electrode facing portion 145, and a connecting portion 147 that connects the electrode facing portion 145 and the interconnector facing portion 146, and is formed of, for example, nickel, a nickel alloy, stainless steel, or the like. The electrode facing portion 145 is in contact with the surface of the fuel electrode 116 on the negative Z-axis direction side (the side opposite to the side facing the electrolyte layer 112), and the interconnector facing portion 146 is in contact with the surface of the interconnector 150 on the positive Z-axis direction side (the side facing the fuel electrode 116). However, as described above, the unit 102 located at the bottom of the stack 100 does not include the lower interconnector 150, and therefore the interconnector facing portion 146 of the unit 102 is in contact with the surface of the lower end plate 106 on the positive Z-axis direction side. With this configuration, the fuel electrode side current collector 144 electrically connects the fuel electrode 116 and the interconnector 150 (or the lower end plate 106). A spacer 149 made of, for example, mica is disposed between the electrode facing portion 145 and the interconnector facing portion 146. Therefore, the fuel electrode side current collector 144 follows the deformation of the unit 102 due to temperature cycles and reactant gas pressure fluctuations, and the electrical connection between the fuel electrode 116 and the interconnector 150 via the fuel electrode side current collector 144 is maintained well.
[0034] The air electrode side current collector 134 is disposed in the air chamber 166. The air electrode side current collector 134 is composed of a plurality of substantially rectangular prism-shaped current collector elements, and is formed of, for example, ferritic stainless steel. The air electrode side current collector 134 is in contact with the surface of the air electrode 114 on the positive side of the Z axis (opposite the side facing the electrolyte layer 112) and the surface of the interconnector 150 on the negative side of the Z axis (opposite the air electrode 114). However, as described above, since the unit 102 located at the top of the stack 100 does not have an upper interconnector 150, the air electrode side current collector 134 of the unit 102 is in contact with the surface of the upper end plate 104 on the negative side of the Z axis. In this manner, the air electrode side current collector 134 electrically connects the air electrode 114 and the interconnector 150 (or the upper end plate 104). The air electrode side current collector 134 and the interconnector 150 may be formed as an integrated member.
[0035] (Single cell configuration) FIG. 6 is a schematic diagram showing the configuration of a single cell 110 according to this embodiment. FIG. 6 shows a YZ cross-sectional configuration. As described above, the single cell 110 includes the fuel electrode 116, the air electrode 114, and the electrolyte layer 112 provided between the fuel electrode 116 and the air electrode 114. That is, the single cell 110 is a laminate including the fuel electrode 116, the electrolyte layer 112 laminated on the fuel electrode 116, and the air electrode 114 laminated on the electrolyte layer 112. In this embodiment, the electrolyte layer 112 is a solid electrolyte layer. The shape of the single cell 110 viewed from above is, for example, a square with one side of 1 to 10 cm, a rectangle with a long side of 5 to 30 cm and a short side of 3 to 15 cm, or a circle with a diameter of 10 cm.
[0036] The fuel electrode 116 (cathode electrode) in this embodiment is formed using nickel oxide and ceramic particles having oxygen ion conductivity as materials. Nickel oxide (NiO) used as the material of the fuel electrode 116 becomes nickel through a reduction process described later. The fuel electrode 116 is a porous thin plate-shaped sintered body. In this embodiment, the fuel electrode 116 is composed of nickel and YSZ (yttria stabilized zirconia). Examples of ceramic materials having oxygen ion conductivity include YSZ (yttria stabilized zirconia), ScSZ (scandia stabilized zirconia), (Gd, Ce) O2, i.e., GDC (gadolinium doped ceria), (Sm, Ce) O2, i.e., SDC (samarium doped ceria), and LaGaO3 (lanthanum gallate). The ceramic material contained in the fuel electrode may be of one type or of two or more types.
[0037] The fuel electrode 116 functions as a cathode and also as a substrate supporting other layers included in the unit cell 110. The thickness of the fuel electrode 116 is greater than the thickness of the electrolyte layer 112. The substrate may be referred to as a support. Of the thicknesses of the components of the unit cell 110, the thickness of the fuel electrode 116 is the greatest, and the fuel electrode 116 also functions as a support (support substrate, member with the highest rigidity) for the unit cell 110. The ratio (T2 / T1)×100 of the thickness T2 of the electrolyte layer 112 to the thickness T1 of the fuel electrode 116 is preferably set to 0.1 to 5%. The thickness T1 of the fuel electrode 116 is not particularly limited, but is, for example, 0.3 to 3 mm.
[0038] In this embodiment, the anode 116 includes, in order from the electrolyte layer 112 side, an anode functional layer 117 and an anode substrate layer 118 having a porosity greater than that of the anode functional layer 117. This ensures the strength of the anode functional layer 117. The thickness of the anode substrate layer 118 is preferably greater than that of the anode functional layer 117. The porosity of the anode functional layer 117 is not particularly limited, but is preferably 30% or less, and more preferably 25% or less. Also, it is preferably 10% or more, and more preferably 15% or more. The porosity of the anode substrate layer 118 is not particularly limited, but is preferably 60% or less, and more preferably 50% or less. Also, it is preferably 20% or more, and more preferably 30% or more. The anode 116 may be formed of a single layer instead of the anode functional layer 117 and the anode substrate layer 118. The anode substrate layer 118 may have a thickness of, for example, 0.3 to 3 mm, and the anode functional layer 117 may have a thickness of, for example, 5 to 50 μm. The anode functional layer 117 and the anode substrate layer 118 may have the same composition. The anode 116 acquires electrical conductivity by undergoing a reduction process described later. That is, the anode 116 undergoes a reduction process, and the unit cell 110 becomes capable of electrolysis. The material contained in the anode 116 is converted from an insulating material to a conductive material by the reduction process. The conversion from an insulating material to a conductive material is realized by, for example, reducing NiO to Ni. In this embodiment, the reduction process is performed after the anode 116 and the electrolyte layer 112 are co-fired as described later, and the timing of the reduction process may be any of before or after the formation of the stack structure, and before or after the formation of the air electrode, the current collecting film, and the like. Usually, the reduction process is performed after the air electrode is formed and a gas flow path is secured. That is, after the stack structure is formed, a reduction step may be performed by passing a reducing gas (specifically, a gas containing hydrogen) through the stack 100 described below at high temperature.
[0039] The electrolyte layer 112 in this embodiment is a flat plate-shaped member having a substantially rectangular shape when viewed in the Z-axis direction, and is a dense layer. The electrolyte layer 112 is formed of a solid oxide such as YSZ (yttria-stabilized zirconia), ScSZ (scandia-stabilized zirconia), SDC (samarium-doped ceria), GDC (gadolinium-doped ceria), perovskite-type oxide, etc. Examples of perovskite-type oxides include lanthanum gallate-based oxides having a perovskite-type structure. Examples of YSZ include 8YSZ and 10YSZ. In this embodiment, the electrolyte layer 112 is a dense, thin-plate-shaped sintered body made of YSZ. The thickness T2 of the electrolyte layer 112 is not particularly limited, but is, for example, 3 to 30 μm.
[0040] Compressive stress remains in the electrolyte layer 112. Therefore, the residual strain S of the electrolyte layer 112 exhibits a negative value. Here, the residual strain S is expressed by the following formula (1). Conversely, tensile stress remains in the anode 116. This compressive stress and tensile stress may occur as a result of co-firing. The residual strain S of the electrolyte layer 112 preferably satisfies -2.5%≦S≦-0.5%. When the residual strain S is within this range, the occurrence of cracks in the electrolyte layer 112 and the peeling of the electrolyte layer 112 from the anode 116 are further suppressed.
[0041]
number
[0042] The air electrode 114 (anode electrode) is a porous thin plate-like sintered body. Examples of materials contained in the air electrode 114 include lanthanum-containing perovskite complex oxides such as LSCF (lanthanum strontium cobalt ferrite), lanthanum manganite, lanthanum cobaltite, and lanthanum ferrite. The lanthanum-containing perovskite complex oxides may be doped with, for example, strontium, calcium, chromium, cobalt, iron, nickel, and aluminum. Other materials include, for example, palladium, platinum, ruthenium, platinum-zirconia cermet, palladium-zirconia cermet, ruthenium-zirconia cermet, platinum-cerium oxide cermet, palladium-cerium oxide cermet, and ruthenium-cerium oxide cermet. The air electrode 114 can contain the exemplified materials as a main component. The air electrode 114 is rectangular in this embodiment, but can be changed to other shapes. In this embodiment, the air electrode 114 is made of lanthanum strontium cobalt ferrite LSCF (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 The cathode 114 is a porous, thin-plate sintered body made of SiO.sub.2.O3. The thickness T3 of the cathode 114 is not particularly limited, but is, for example, 5 to 150 .mu.m.
[0043] In addition, in order to suppress the occurrence of a phenomenon in which YSZ in the electrolyte layer 112 and strontium in the air electrode 114 react with each other in the single cell 110 during cell fabrication or during operation of the SOEC, causing an increase in electrical resistance between the electrolyte layer 112 and the air electrode 114, a reaction prevention layer may be interposed between the electrolyte layer 112 and the air electrode 114. The reaction prevention layer is not particularly limited, but is preferably, for example, a dense, thin-plate sintered body made of ceria. Examples of ceria include, but are not particularly limited to, GDC (gadolinium-doped ceria) and SDC (samarium-doped ceria). The thickness of the reaction prevention layer is, but is not particularly limited to, for example, less than 20 μm.
[0044] In this SOEC single cell 110, water vapor is supplied to the fuel electrode 116, and a gas containing oxygen is supplied to the air electrode 114. At the same time, a current is passed between the fuel electrode 116 and the air electrode 114, causing a chemical reaction as shown in the following formula. As a result, hydrogen is generated from the fuel electrode 116, and oxygen is generated from the air electrode 114. H2O+2e - →H2+O 2- (Location: Fuel electrode 116) O 2- →(1 / 2)·O2+2e - (At: Air pole 114)
[0045] In this SOEC single cell 110, a conductive connection member (interconnector 150 (see FIG. 2)) for collecting current is usually joined and fixed to each of the fuel electrode 116 and the air electrode 114 with a bonding agent, and a potential difference is applied via each interconnector to allow a current to flow. Hydrogen gas generated from the fuel electrode is collected.
[0046] The fuel electrode 116 is supplied with a fuel gas containing water vapor at a rate of, for example, 90 to 140 liters / (min cm 2 ) and may be used at a flow rate of 100 to 130 liters / (min cm 2 ) may be supplied for use. In the case of co-electrolysis, a gas containing water vapor and CO2 may be supplied as the fuel gas. In a stack in which cells are stacked in multiple stages, the amount of fuel gas input by a blower, pump, etc. naturally increases in proportion to the number of layers.
[0047] The air electrode 114 is supplied with a gas containing oxygen at a rate of, for example, 20 to 60 liters / (min cm 2 ) and may be used at a flow rate of 30 to 50 liters / (min cm 2 ) may be supplied and used. As the gas containing oxygen, oxygen gas or air may be used. In a stack in which cells are stacked in multiple stages, the amount of gas input to the air electrode side by a blower, pump, etc. naturally increases in proportion to the number of layers.
[0048] The volume of the air chamber 166 facing the air electrode 114 is not particularly limited, but is preferably 8 cm 3 ~13cm 3 Preferably, 9 cm 3 ~11cm 3 Here, the volume of the air chamber 166 facing the air electrode 114 refers to the volume per cell, and does not include the volume occupied by the current collecting members and the like.
[0049] A-2: Manufacturing method of single cell FIG. 7 is a process diagram showing an example of a method for manufacturing a single cell 110 of an SOEC.
[0050] (Preparation of anode green sheet: Process P110) Organic beads as a pore former, butyral resin, DOP as a plasticizer, a dispersant (Floren G-700 (Kyoeisha Chemical Co., Ltd.)), and a mixed solvent of toluene and ethanol are added to a mixed powder of NiO (nickel oxide) powder and YSZ powder, and mixed in a ball mill to prepare a slurry. The organic beads are spherical particles formed of polymers such as polymethyl methacrylate and polystyrene. The organic beads are burned during firing, which will be described later, and the places where the organic beads were present become pores. The obtained slurry is thinned by a doctor blade method to prepare a green sheet for anode with a predetermined thickness (for example, 200 μm to 300 μm). The mixing ratio of NiO powder and YSZ powder when preparing the green sheet for anode can be appropriately set as long as the performance is satisfied. For example, the mixing ratio of NiO (nickel oxide) powder and YSZ powder may be such that the volume ratio of NiO is 20 to 60 volume %, and the volume ratio of YSZ is 40 to 80 volume %.
[0051] (Preparation of green sheet for electrolyte layer: Process P120) Butyral resin, DOP as a plasticizer, dispersant (Floren G-700 (Kyoeisha Chemical Co., Ltd.)), and a mixed solvent of toluene and ethanol are added to the YSZ powder, and then mixed in a ball mill to prepare a slurry. The obtained slurry is thinned by a doctor blade method to prepare a green sheet for an electrolyte layer of a predetermined thickness (for example, 10 μm).
[0052] (Preparation of Laminate of Electrolyte Layer 112 and Fuel Electrode 116: Step P130) The green sheet for the fuel electrode and the green sheet for the electrolyte layer are attached and degreased at a predetermined temperature (for example, about 280°C). Furthermore, the laminate of the green sheets after degreasing is fired at a predetermined temperature (for example, about 1350°C). In this way, a laminate of the electrolyte layer 112 and the fuel electrode 116 is obtained. The inventors of the present application have found that by adjusting the temperature increase rate and the temperature decrease rate during this firing, stress can be alleviated, dimensional changes can be suppressed, and the occurrence of cracks in the electrolyte can be suppressed. Specifically, the temperature increase rate is preferably 3°C / min or less, more preferably 2°C / min or less, even more preferably 1.5°C / min or less, and even more preferably 1.3°C / min or less. Moreover, the temperature increase rate is preferably 0.3°C / min or more, more preferably 0.5°C / min or more, even more preferably 0.8°C / min or more, and even more preferably 1.0°C / min or more. The temperature drop rate is preferably 2° C. / min or less, more preferably 1.5° C. / min or less, and even more preferably 1.3° C. / min or less. The temperature drop rate is preferably 0.3° C. / min or more, more preferably 0.5° C. / min or more, and even more preferably 0.8° C. / min or more.
[0053] The method for producing the laminate of the electrolyte layer 112 and the fuel electrode 116 is not limited to the above method, and may be, for example, the following method. A slurry is produced by adding polyvinyl alcohol (PVA) as a binder to a mixture of NiO powder and YSZ powder, and the slurry is dried and granulated by a spray dryer, and a green body of the fuel electrode is formed by a mold press molding method. Next, water and a binder are added to the YSZ powder, and the mixture is mixed in a ball mill for 24 hours to produce a slurry. The slurry is applied and molded on the green body of the fuel electrode to laminate and form a green body of the electrolyte. The laminate of the green bodies may be co-sintered in air in an electric furnace (in an oxygen-containing atmosphere) at, for example, 1350° C. to form a laminate of the fuel electrode 116 and the electrolyte layer 112. A tape lamination method, a printing method, or the like may be used to form a film that will later become the electrolyte layer 112 on the fuel electrode 116.
[0054] (Formation of the air electrode 114: step P140) A paste for an air electrode is prepared by mixing LSCF powder, polyvinyl alcohol as an organic binder, and butyl carbitol as an organic solvent, and adjusting the viscosity. The adjusted paste for an air electrode is applied to the surface of the electrolyte layer 112 in the laminate of the electrolyte layer 112 and the fuel electrode 116 described above, for example, by screen printing, and dried. The laminate with the paste for an air electrode applied thereto is fired at a predetermined firing temperature (for example, 1100°C). This forms the air electrode 114, and a single cell 110 including the fuel electrode 116, the electrolyte layer 112, and the air electrode 114 is fabricated.
[0055] (Reduction process: process P150) Thereafter, a reduction step is performed to reduce the fuel electrode 116 so that the single cell 110 can be operated to produce hydrogen. That is, this step is a step in which the fuel electrode 116, which is in a non-reduced state, is turned into a reduced state by heat treatment in a reducing atmosphere. In the reduction step, NiO contained in the fuel electrode 116 is reduced to Ni. The reduction step is achieved, for example, by exposing the fuel electrode 116 to a hydrogen atmosphere at a predetermined temperature for a predetermined time. The reducing gas used in the reduction step is not limited to hydrogen, and may be other gases capable of reducing NiO to Ni, such as methane gas, and the concentration of the reducing gas is also not limited. The reducing gas having a reducing agent concentration of less than 100% by volume may contain, for example, nitrogen gas in addition to hydrogen gas.
[0056] The manufacturing method of the SOEC of this embodiment includes the reduction step described above. When the dimension of the fuel electrode 116 at the beginning of the reduction step is LI, the dimension of the fuel electrode 116 at the end of the reduction step is LR, and the dimensional change amount ΔL (%) is ΔL = {(LR-LI) / LI} × 100, ΔL (%) is -0.05% or more and 0% or less. The beginning of the reduction step means immediately after the start of the reduction step, and the end of the reduction step means the time when the reduction step ends. The reduction step is performed at 700°C to 800°C. Generally, in SOFCs, oxygen is consumed at the fuel electrode during use, so the gas pressure decreases, but in SOECs, oxygen is generated on the air electrode 114 side during use, so the gas pressure increases and a different stress is applied to the SOFC. However, the present inventors have found that in the manufacturing method of the SOEC, by setting ΔL (%) within the range of -0.05% to 0%, it is possible to suppress the occurrence of cracks in the electrolyte layer 112 during use of the SOEC. The durability of electrolyte layer 112 can be improved by suppressing the occurrence of cracks in electrolyte layer 112. Although the mechanism behind this is unclear, it is believed that when ΔL satisfies the above-mentioned condition, the difference between the dimensional change rate of electrolyte layer 112 and the dimensional change rate of anode 116 is kept small, and as a result, it is believed that the occurrence of cracks in electrolyte layer 112 is suppressed when an SOEC is used. In this disclosure, "dimension of anode 116" refers to the thickness of anode 116 at the center, and "dimension of electrolyte layer 112" refers to the thickness of electrolyte layer 112 at the center.
[0057] The inventors of the present application have found that the value of ΔL can be adjusted by adjusting the rate of temperature increase and decrease during the above-mentioned firing. In addition, ΔL can be adjusted to within the above-mentioned range by adjusting the mixing ratio of the nickel oxide powder and the ceramic powder having oxygen ion conductivity, which are the materials for forming the fuel electrode 116.
[0058] Furthermore, the inventors of the present application have discovered that the residual strain S (%) generated in the solid electrolyte layer (electrolyte layer 112), which is expressed by the following formula (1), can be more efficiently prevented from generating cracks in the electrolyte layer 112 during use of the SOEC by making the residual strain S (%) greater than or equal to -2.5% and less than or equal to -0.5%.
[0059]
number
[0060] Although the mechanism behind this is unclear, the following mechanism is presumed. In other words, it is presumed that a residual strain S between -2.5% and -0.5% acts to suppress dimensional change. Here, for example, the residual strain S can be adjusted by adjusting the compounding ratio of nickel oxide and ceramic material. The greater the proportion of nickel oxide, the greater the tendency for shrinkage during firing, and as a result, the residual strain S tends to swing in the negative direction. On the other hand, the smaller the proportion of nickel oxide, the less the tendency for shrinkage during firing to be, and as a result, the residual strain S tends to approach 0.
[0061] (test) In this test, multiple types of test specimens (sintered bodies) were produced for the SOEC according to the above embodiment, each having a different combination of volume ratios of NiO and YSZ in the fuel electrode 116. Specifically, as shown in Table 1, 14 types of conditions (combinations) were prepared, and one test specimen was produced for each condition.
[0062] In each of these test specimens, the thickness T1 of the fuel electrode 116 (NiO-YSZ) was 400 μm, the thickness T2 of the electrolyte layer 112 (8YSZ) was 10 μm, and the thickness T3 of the air electrode 114 (LSCF) was 80 μm. In addition, the shape of each of these test specimens viewed from above was a square with sides of 10 cm.
[0063] In Table 1, the volume ratio and average particle size of NiO and YSZ are values after sintering and before the reduction process. This volume ratio was calculated by cutting the sintered bodies produced at the same time, photographing five cross sections per sintered body with a SEM (Scanning Electron Microscope)-EDX (Energy Dispersive X-ray Spectroscopy), analyzing the obtained images, and then calculating the average value. In the table, "YSZ volume ratio" means the ratio of the total volume of YSZ contained in the fuel electrode 116 to the total volume of the fuel electrode 116 (including the volume of the space occupied by the pores). Also, "NiO volume ratio" means the ratio of the total volume of NiO contained in the fuel electrode 116 to the total volume of the fuel electrode 116 (including the volume of the space occupied by the pores).
[0064] Hydrogen was used as the reducing agent in the reducing gas. A reducing gas with a reducing agent concentration of 100% by volume, i.e., a reducing gas consisting only of hydrogen, was used. Air was used on the air electrode side during the reduction process.
[0065] For the prepared test sample (sintered body), the dimension LI of the fuel electrode 116 at the beginning of the reduction process was measured. After that, the test sample was heated to 700° C., and a reducing gas was supplied to the fuel electrode to carry out the reduction process. Then, the dimension LR of the fuel electrode 116 (reduced body) at the end of the reduction process was measured. The amount of dimensional change before and after the reduction process, ΔL={(LR-LI) / LI}×100, is shown in Table 1. Here, the mass of the test sample before and after the reduction process was measured, and by comparing the measured value with the calculated value of the mass calculated from the volume ratio, it was confirmed that the sintered body was changed into the reduced body by the reduction process.
[0066] The test specimen thus fabricated was then heated again from room temperature to 700°C, hydrogen and water vapor were passed through the fuel electrode side, air was passed through the air electrode side, and an electric current was passed through the test specimen to conduct an electrolysis test, and the test specimen was then cooled to room temperature. This cycle was repeated five times (thermal cycle electrolysis test). The change in open circuit voltage (OCV) between the first and fifth thermal cycle electrolysis tests, and the presence or absence of cracks on the surface of the electrolyte layer 112 after the test were observed using a binocular microscope. The results are shown in Table 1.
[0067] [Table 1]
[0068] It can be seen from Table 1 that ΔL can be set within the range of −0.05 to 0% by adjusting the various volume ratios of NiO and YSZ.
[0069] Also, in the test sample (condition: No. 1) where ΔL exceeded 0%, the volume ratio of YSZ was large, so shrinkage after reduction was small, which is thought to have led to a large change in OCV and the occurrence of cracks in the electrolyte layer 112. On the other hand, in the test sample (condition: No. 14) where ΔL was less than -0.05%, the volume ratio of NiO and pores was large, so shrinkage after reduction was large, which is thought to have led to a large change in OCV and the occurrence of cracks in the electrolyte layer 112.
[0070] From the above, it has been found that by setting ΔL within the range of −0.05 to 0%, it is possible to provide a highly reliable SOEC cell in which problems such as the occurrence of cracks on the surface of the electrolyte layer 112 do not occur.
[0071] In test samples (conditions: Nos. 2, 5, 8, and 13) in which ΔL was -0.05% to 0% but the residual strain S was outside the range of -2.5% to -0.5%, after the thermal cycle test, the difference in OCV from the first test was 0.04 to 0.05 V. In these electrolytic cells, the presence of cracks was not confirmed in the electrolyte layer 112 using a binocular microscope, but when the difference in OCV was 0.02 to 0.05 V, it is believed that minute cracks (microcracks) had occurred.
[0072] The present invention is not limited to the above-mentioned embodiment, and can be realized in various configurations without departing from the spirit of the present invention. For example, the technical features in the embodiments corresponding to the technical features in each aspect described in the Summary of the Invention column can be appropriately replaced or combined to solve some or all of the above-mentioned problems or to achieve some or all of the above-mentioned effects. Furthermore, if a technical feature is not described as essential in this specification, it can be appropriately deleted.
[0073] The electrolysis cell only needs to have the fuel electrode 116, the electrolyte layer 112, and the air electrode 114, and the presence or absence of other components, as well as the shape, material, dimensions, etc. of each component can be changed. For example, the configuration of the electrolysis cell may be changed as follows. (1) The shape of the electrolytic cell may be, for example, anode-supported, flat, cylindrical, flat, vertically striped, horizontally striped, for one-end-supported stacks, for both-end-supported stacks, etc. Also, the cross section of the cell may be elliptical. (2) The configurations presented as different forms can be combined with each other. [Explanation of symbols]
[0074] 22, 22A, 22B, 22D, 22E...bolts, 24...nuts, 26...insulating sheet, 27...gas passage member, 28...main body, 29...branching portion, 100...stack, 102...unit, 104, 106...end plates, 108...communication hole, 110...single cell, 112...electrolyte layer, 114...air electrode, 116...fuel electrode, 117...fuel electrode functional layer, 118...fuel electrode substrate layer, 120...separator, 121...hole, 124...joint, 130...air electrode side frame, 131...hole, 132...air electrode gas supply communication hole, 133...air electrode gas discharge communication hole , 134...air electrode side current collector, 140...fuel electrode side frame, 141...hole, 142...fuel gas supply passage, 143...fuel gas exhaust passage, 144...fuel electrode side current collector, 145...electrode opposing portion, 146...interconnector opposing portion, 147...connecting portion, 149...spacer, 150...interconnector, 161...air electrode gas supply manifold, 162...air electrode gas exhaust manifold, 166...air chamber, 171...fuel gas supply manifold, 172...fuel gas exhaust manifold, 176...fuel chamber, FG...fuel gas, FOG...fuel off-gas
Claims
1. A method for manufacturing a solid oxide electrolysis cell comprising an anode, an air electrode, and a solid electrolyte layer provided between the anode and the air electrode, the method comprising the steps of: The fuel electrode is formed using nickel oxide and a ceramic material having oxygen ion conductivity as materials, The fuel electrode has pores formed therein, The method includes a step of converting the fuel electrode from a non-reduced state into a reduced state by heat treatment in a reducing atmosphere, The dimension of the fuel electrode at the beginning of the process is designated as LI, The dimension of the fuel electrode at the end of the process is defined as LR, When the dimensional change rate ΔL (%) is ΔL = {(LR-LI) / LI} x 100, ΔL (%) is −0.05% or more and 0% or less; A method for manufacturing a solid oxide electrolysis cell.
2. 2. The solid oxide electrolysis cell according to claim 1, The residual strain S (%) generated in the solid electrolyte layer is represented by the following formula (1) and is −2.5% or more and −0.5% or less. A method for manufacturing a solid oxide electrolysis cell. [0010]
3. The solid oxide electrolysis cell according to claim 1 or 2, the anode includes, in order from the solid electrolyte layer side, an anode functional layer and an anode substrate layer having a porosity greater than that of the anode functional layer; A method for manufacturing a solid oxide electrolysis cell.
4. The solid oxide electrolysis cell according to claim 1 or 2, The fuel electrode is supplied with a fuel gas containing water vapor at a rate of 100 to 130 liters / min.cm 2 ) is supplied and used at a flow rate of A method for manufacturing a solid oxide electrolysis cell.
5. The solid oxide electrolysis cell according to claim 1 or 2, The air electrode is supplied with an oxygen-containing gas at a rate of 30 to 50 liters / min.cm 2 ) is supplied and used at a flow rate of A method for manufacturing a solid oxide electrolysis cell.
6. The solid oxide electrolysis cell according to claim 1 or 2, The fuel electrode is supplied with a fuel gas containing water vapor at a rate of 100 to 130 liters / min.cm 2 ) is supplied and used at a flow rate of The air electrode is supplied with an oxygen-containing gas at a rate of 30 to 50 liters / min.cm 2 ) is supplied and used at a flow rate of A method for manufacturing a solid oxide electrolysis cell.
7. The solid oxide electrolysis cell according to claim 1 or 2, The volume of the air chamber facing the air electrode is 9 cm 3 ~11cm 3 That is, A method for manufacturing a solid oxide electrolysis cell.
Citation Information
Patent Citations
Electrochemical reaction cell stack
JP2023080459A
Cited By
Solid oxide electrolysis cell and use thereof
WO2025169896A1